"It wasn't just for me": Motivations and implications of genetic testing for women at a low risk of hereditary breast and ovarian cancer syndrome. Issue 8 (9th July 2020) - Gill, Gulvir; Beard, Catherine; Storey, Kirsty; Taylor, Shelby; Sexton, Adrienne
Abstract: Objective: Genetic testing for hereditary breast and ovarian cancer (HBOC) due to pathogenic variants in BRCA1 or BRCA2 is why most women present to familial cancer centers. Despite being assessed as low risk for HBOC, many women proceed with genetic testing. This study explored the genetic testing experiences of unaffected women at low risk of HBOC to clarify what motivates these women to have testing, and what are the implications of the results. Methods: A qualitative approach was taken. Participants included women who had genetic testing for HBOC from 2016‐2018 at the Parkville Familial Cancer Centre in Melbourne, Australia. In‐depth, semi‐structured interviews were conducted, and thematic analysis was undertaken on transcripts; transcripts were coded, codes were organized into a hierarchical system of categories/subcategories, and key themes were identified. Results: Analysis of 19 transcripts identified five themes: family underpinned all motivators for HBOC genetic testing; health professionals were influential throughout the process; participants were planning for a positive result; results influenced screening‐anxiety and frequency; and negative results gave participants relief in many different ways. The three participants with positive results reported feeling shocked at the results and empowered giving this information to family members. Conclusions: Women at low HBOC risk may be motivated to seek genetic testing, and access to this is increasingly offered through non‐genetic health professionals. Professionals can support clients through genetic testing by recognizing familial experiences, providing accurate information, addressing risk perceptions, and understanding cancer anxiety felt by many women.